Celiac Disease From the Bench to the Clinic - Rodrigo, Luis; Hernández-Lahoz, Carlos (IntechOpen, 2019)
Celiac disease (CD) occurs in about 1% of people worldwide. Diagnosis rates are increasing due to a true rise in incidence, rather than increased awareness and detection. CD affects genetically susceptible individuals who are triggered by the ingestion of gluten. The disease has many clinical manifestations, ranging from severe to minimally symptomatic or non-symptomatic presentations. Diagnosis requires the presence of duodenal chronic inflammation, and most patients have circulating antibodies against tissue transglutaminase. Our understanding of the basic and clinical aspects of CD increases, which is as a major health problem of almost global occurrence. Case finding, distinguishing CD from other gluten-sensitive conditions, better care, and balanced use of resources are the current challenges.